Analisis Pengaruh Keadilan Organisasi dan Quality of Work Life Terhadap Kepuasan Kerja Karyawan Honorer BKAD Kota Tangerang Selatan - Fadhila Harfiani; Priyo Susilo; Abdul Rauf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The study aims to determine and analyze the effect of organizational justice on employee job satisfaction, the effect of quality of work life on employee job satisfaction and to determine the effect of organizational justice and quality of work life on employee job satisfaction partially or simultaneously. Using an associative method with a quantitative approach. This study uses SPSS version 30. The population in this study were all honorary employees of the South Tangerang City BKAD totaling 62 people. The sampling technique used was a saturated sample, thus the sample used in this study amounted to 62 honorary employees of the South Tangerang City BKAD as respondents. Sampling using random sampling technique using a questionnaire instrument to collect data. The results of the study indicate that Organizational Justice has an effect on Employee Job Satisfaction, Quality of Work Life has an effect on Employee Job Satisfaction, Organizational Justice and Quality of Work Life have an effect on Employee Job Satisfaction, The implications of the study indicate that Organizational Justice and Quality of Work Life have an effect and are able to increase Employee Job Satisfaction.